Primary adrenal lymphoma and its mimics: clinico-radiological differential diagnosis - Kłosowski, Przemysław; Brzezińska, Natalia; Kmieć, Piotr; Okroj, Dominika; Zembrzuska, Sonia; Kujawa, Mariusz; Babińska, Anna; Świątkowska-Stodulska, Renata (Frontiers in Endocrinology, 2025)
PurposePrimary adrenal lymphoma (PAL) is a rare malignancy with limited data on its characteristics. It can pose diagnostic challenges in differentiating it from other adrenal masses, such as atypical adrenal adenoma (ADE), pheochromocytoma (PCC), and adrenocortical carcinoma (ACC). This study aimed to characterize patients with PAL and compare their clinical, hormonal, and radiological features with other primary adrenal lesions whose computed tomography characteristics do not match those of a typical adenoma.MethodsThis retrospective, single-center study included four patient cohorts: PAL (n=12), ADE (n=31), PCC (n=18), and ACC (n=19), treated at a tertiary care hospital between January 2013 and January 2024.ResultsThe histopathological type of all PAL cases was diffuse large B-cell lymphoma (DLBCL). The median age at diagnosis was 70.5 (51–76) years. The diagnosis was more prevalent in males (sex ratio 1.4). Bilateral adrenal involvement was significantly more frequent in PAL patients. Clinical symptoms included general health deterioration (100%), weight loss (75%), abdominal pain (58%) and fever (41.7%). Laboratory assessments showed a higher prevalence of anemia in PAL patients compared to ADE and PCC patients. PAL cases exhibited elevated lactate dehydrogenase (LDH) and β2-microglobulin as well as lipid profile abnormalities. Radiologically, PAL lesions were predominantly homogeneous, with a median tumor size of 78.5 (20-100.5) mm. All lesions exhibited an attenuation value > 20 Hounsfield Unit (HU) and lacked calcifications. Malignant lymph node involvement was significantly more frequent in the PAL than other cohorts.ConclusionPAL should be included in the differential diagnosis of adrenal masses, particularly in cases of bilateral involvement. This study offers insights into its clinical presentation and highlights distinguishing features compared to other primary adrenal malignancies.